The Effectivity of Nutrition Education using E-Booklet on Knowledge and Attitude about Anemia among Adolescent Girls in Turen Malang - Paramita, Farah; Rachmawati, Windi Chusniah; Ekawati, Rany; Aulia Pherenis, Haura Salwa; Septiani, Selsa Tri; Awaliahmunazila, Meisya (Preventia: The Indonesian Journal of Public Health, 2024)
One of the nutritional problems of adolescent female in Southeast Asia is iron deficiency anemia, with an estimated 25-40 percent of adolescent female experiencing mild to severe anemia. The impact of this on teenagers is a decline in academic abilities at school due to a lack of enthusiasm for learning and concentration on learning. This research aims to determine the effect of e-booklet anemia prevention media on young women at SMAN 1 Turen. This research uses an experimental method, namely a pre-experimental design with a one group pretest-posttest approach. The subjects of this research were 50 female students. The results of the study showed that there was an influence of e-booklet anemia prevention media on the level of knowledge (p value is 0.000 less than 0.05) and attitudes (p value is 0.032 less than 0.05) of young women at SMAN 1 Turen. There was a significant influence on knowledge and attitudes before and after being given treatment in the form of education using e-booklet media